Gene redundancy and gene compensation of insulin-like peptides in the oocyte development of bean beetle - Li, Yongqin; Fang, Zheng; Tan, Leitao; Wu, Qingshan; Liu, Qiuping; Wang, Yeying; Weng, Qingbei; Chen, Qianquan (PloS one, 2024)
Bean beetle ( Callosobruchus maculatus ) exhibits clear phenotypic plasticity depending on population density; However, the underlying molecular mechanism remains unknown. Compared to low-density individuals, high-density individuals showed a faster terminal oocyte maturity rate. Four insulin-like peptide (ILP) genes were identified in the bean beetle, which had higher expression levels in the head than in the thorax and abdomen. The population density could regulate the expression levels of CmILP1-3 , CmILP2-3 , and CmILP1 as well as CmILP3 in the head, thorax, and abdomen, respectively. RNA interference results showed that each CmILP could regulate terminal oocyte maturity rate, indicating that there was functional redundancy among CmILPs . Silencing each CmILP could lead to down-regulation of some other CmILPs , however, CmILP3 was up-regulated in the abdomen after silencing CmILP1 or CmILP2 . Compared to single gene silencing, silencing CmILP3 with CmILP1 or CmILP2 at the same time led to more serious retardation in oocyte development, suggesting CmILP3 could be up-regulated to functionally compensate for the down-regulation of CmILP1 and CmILP2 . In conclusion, population density-dependent plasticity in terminal oocyte maturity rate of bean beetle was regulated by CmILPs , which exhibited gene redundancy and gene compensation.